Cleanliness and Hygiene Perceptions of Primary School Students in 6th, 7th, and 8th Gradess - Kahveci, Gokhan; Demirtas, Zulfu (Pegem Akad Yayincilik Egitim Danismanlik Hizmetleri Tic Ltd Sti, 2012)
The aim of this research is to determine the perception of the students of 6th, 7th and 8th grades. The research is designed by survey model. The population of the research consists of the students that are educated in 2010-2011 education year in 6th, 7th and 8th classes of the schools that are located in the centre of Kovancilar of the city Elazig. The research was done by the help of the population the research. The sample of the research was not taken into consideration. The cleaning and hygiene scale has been used as a measuring tool. For the analysis of the research t-Test, Mann-Whitney U test, One Way Anova analysis and Kruskal Wallis have been helpful to us. As a result of the research, the perception of the personnel hygiene and care has the highest importance, but the perception of the cleaning of the school and its environment is at the lowest point and also it is known that the students from 6th classes have higher perception on Cleaning and Hygiene'' than the students from 7th and 8th classes.
Keywords: Cleaning; Hygiene; School; School hygiene; Primary school